Animal farm - Orwell, George (London ; New York : Penguin, 2008)
A satire on totalitarianism in which farm animals overthrow their human owner and set up their own government.
Originally published: London: Martin Secker & Warburg, 1945.
Keywords: Farms; Livestock; Political corruption; Farms; Livestock; Political corruption